How to get started and keep going : - Hughes, Stella (United Nations Education, Scientific and Cultural Organization (UNESCO), 2004)
There are growing numbers of grass-root communication and information service providers in the developing countries today. They are operating community radio stations, multipurpose telecentres, information centres, community learning centres and – in a few cases – community multimedia centres (CMCs) that already combine both radio and telecentre facilities. This book is intended to be of use to all those wanting to become involved or already involved in such initiatives – staff and managers, community groups, NGOs working for community empowerment, communication planners supporting development activities, trainers and project partners. It will obviously be of particular interest to those operating or considering starting a CMC as it covers the full range of topics linked to community broadcasting and to telecentre operations.